Disaggregation at High Volume Exclusion: An “Overcrowding” Effect - Koch, Leon; Baier, Dominik; Rajput, Satyendra; König, Benedikt; Tiemann, Michael; Ebbinghaus, Simon; Nayar, Divya; Huber, Klaus (The Journal of Physical Chemistry B)

Innovative teaching with actionbound: Digital pathways in chemistry education - a practical example from ComeNet Chemistry in the ComeMINT Project - Weiser, David; Ditter, Rebecca; Ditter, David; Siepmann, Karin; Grandrath, Rebecca; Fechner, Sabine; Sommer, Katrin; Bohrmann-Linde, Claudia; Rubner, Isabel (International conference New Perspective on Science Education)

Empirische Befunde der Interessenforschung der Fächer Biologie, Chemie und Physik im Primar- und Sekundarbereich seit 2012 – Ein systematisches Review - Habig, Sebastian; Großmann, Nadine; Schmid, Andrea M.; van Vorst, Helena; Fechner, Sabine; Wilde, Matthias (Interesse revisited)

Interessenförderung im Physik- und Chemieunterricht – Eine Bestandsaufnahme - Zöchling, Sarah; Pletschacher, Laura; Maurer, Christian; Berger, Roland; Lindmaier, Kerstin; Fechner, Sabine; Wodzinski, Rita (Interesse revisited)

Parameter Averaging in Link Prediction - Sapkota, Rupesh; Demir, Caglar; Sharma, Arnab; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Thirteenth International Conference on Knowledge Capture(K-CAP 2025))
Ensemble methods are widely employed to improve generalization in machine learning. This has also prompted the adoption of ensemble learning for the knowledge graph embedding (KGE) models in performing link prediction. Typical approaches to this end train multiple models as part of the ensemble, and the diverse predictions are then averaged. However, this approach has some significant drawbacks. For instance, the computational overhead of training multiple models increases latency and memory overhead. In contrast, model merging approaches offer a promising alternative that does not require training multiple models. In this work, we introduce model merging, specifically weighted averaging, in KGE models. Herein, a running average of model parameters from a training epoch onward is maintained and used for predictions. To address this, we additionally propose an approach that selectively updates the running average of the ensemble model parameters only when the generalization performance improves on a validation dataset. We evaluate these two different weighted averaging approaches on link prediction tasks, comparing the state-of-the-art benchmark ensemble approach. Additionally, we evaluate the weighted averaging approach considering literal-augmented KGE models and multi-hop query answering tasks as well. The results demonstrate that the proposed weighted averaging approach consistently improves performance across diverse evaluation settings.
Keywords: Knowledge Graphs; Embeddings; Ensemble Learning

Kindermädchen – Von ‚strebsamen Mädchen‘, fliegenden Regenschirmen und neuen Gewändern eines (nicht) ausgestorbenen Berufes - Göddertz, Nina (Soziale Frauenberufe in Ost und West)

Dienstmädchen – von romantisierten Zuschreibungen und menschenunwürdigen Arbeits- und Lebensbedingungen, damals wie heute. - Göddertz, Nina (Soziale Frauenberufe in Ost und West)

Insights into the current situation of technological education at primary schools – illustrated by the example of Germany - Schneider, Lea; Tenberge, Claudia (The 42nd Pupils' Attitudes Towards Technology Conference)

Visitor Revival Propositions for Cultural Institutions – A Service Science Perspective - Hansmeier, Philipp; Althaus, Maike (Journal of Service Management Research)

ARTIFICIAL INTELLIGENCE IN DIGITAL SERVICE ECOSYSTEMS – A TAXONOMY APPROACH - Hansmeier, Philipp; Schäfer, Jannika Marie (Thirty-Third European Conference on Information Systems)

CONCEPTUALIZING A CUSTOMER EXPERIENCE FRAMEWORK FOR HYBRID (PHYSICAL-DIGITAL) SERVICE ECOSYSTEMS - Hansmeier, Philipp (Thirty-Third European Conference on Information Systems)

Service Innovation through Data Ecosystems – Designing a Recombinant Method - Hansmeier, Philipp; zur Heiden, Philipp; Beverungen, Daniel (Proceedings of the 20th International Conference on Wirtschaftsinformatik (WI25))

Ecosystem-Level Customer Experience with Smart Service: Insights from a Systematic Scoping Literature Review - Hansmeier, Philipp; Beverungen, Daniel (Journal of Service Management Research)
Smart service is fundamentally transforming customer experience in both commercial and private contexts. While the information systems and service disciplines have explored the properties and implementation of smart service, there is a gap in understanding how smart service relates to customer experience at the ecosystem level. With the increasing prominence of digital platforms and data spaces, this ecosystem perspective will become crucial for the success of smart service. We report findings from a systematic scoping literature review on smart service themes and related customer experience concepts. Our analysis of 26 high-quality papers reveals three key insights: (1) smart service systems play a pivotal role in enabling customer experience, (2) customer experience in smart service scenarios is often co-created through “hybrid” customer journeys, and (3) these scenarios are subject to an ecosystem-level. Additionally, we identify smart service fundamentals, embeddedness levels, and business innovation as core themes that shape ecosystem-level customer experience.

Molecular Orientation‐Dependent Photonic Spin–Orbit Coupling in Organic Microcavities Filled with 2D Polymorphic Crystals - Ji, Ying; Ma, Xuekai; Huang, Han; Deng, Yibo; Wang, Pingyang; Long, Teng; Li, Yuan; Zhao, Ruiyang; Li, Yunfei; An, Cunbin; Schumacher, Stefan; Gu, Chunling; et al. (Laser & Photonics Reviews)
ABSTRACT Effective manipulation of photonic spin–orbit coupling (SOC) in microcavities is of fundamental importance within topological photonics and applications. Anisotropic organic single‐crystalline materials can induce abundant SOC phenomenon due to their flexible tunability of molecular geometries, however, the intrinsic relationship between molecular geometries/orientations in 3D space and photonic SOC is lacking. In this study, we design two kinds of 2D organic polymorphs for the construction of organic microcavities to investigate the structure‐performance relationships. In two polymorphic microcavities, two distinctive photonic SOC phenomena are observed regardless of the in‐plane anisotropy of organic polymorphs. Theoretical analysis indicates that the photonic SOC strength is strongly influenced by the synergies between the crystal anisotropy and the tilted collective molecular transition dipole moment. Our results uncover the correlation mechanism between the structure of molecules and photonic SOC and open an avenue to engineer complex photonic SOC by use of organic microstructures towards the development of diverse integrated photonic devices.

Tuning polariton vortices in an asymmetric ring potential - Ai, Qiang; Ma, Xuekai; Barkhausen, Franziska; Zhai, Xiaokun; Xing, Chunzi; Yang, Xinmiao; Wang, Peilin; Liu, Tianyu; Zhang, Yong; Gu, Yazhou; Li, Peigang; Li, Zhitong; et al. (Applied Physics Letters)
Exciton polariton condensates are macroscopic coherent states in which topological excitations can be observed. In this work, we observe the excitation of the vortices and realize tuning the topological charge by manipulating the pumping configurations. Using a digital micromirror device, we constructed an annular pumping pattern where the inner and outer rings can be easily tuned. Both the number and the topological charge of the vortices can be changed by slightly tuning the inner ring position against the outer ring. The experimental results can be reproduced in theory by the Gross–Pitaevskii equation. Our work offers to generate and manipulate vortices in exciton polariton condensates using a straightforward optical method.

Higher-order dark solitons and control dynamics in microcavity polariton condensates - Sun, Jinming; Chen, Manna; Schumacher, Stefan; Hu, Wei; Ma, Xuekai (Physical Review B)

In Situ PM‐IRRAS and XPS Analysis of Nitrogen Plasma Surface Modification of Polylactide Thin Films - Gołębiowska, Sandra; Voigt, Markus; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Surface and Interface Analysis)
ABSTRACT Spin‐coated polylactide (PLA) thin films were exposed to nitrogen plasma for varying time intervals. The progressive etching of the PLA film in direct contact with the nitrogen plasma was monitored in situ using polarization modulated infrared reflection absorption spectroscopy (PM‐IRRAS). No appreciative changes in composition were seen with PM‐IRRAS, indicating that the etching did not significantly affect the bulk composition. Atomic force microscopy characterization of the plasma‐etched films showed that the PLA films are homogeneously etched. Subsequent ex situ XPS analysis of the treated surface revealed the presence of C‐N bonds in the surface‐near region that could be associated with amino and/or amide surface species. PLA films were also alternatively exposed to nitrogen ion beams produced by an electron‐cyclotron‐resonance (ECR) plasma source and were investigated in vacuo by XPS. This treatment revealed the partial substitution of surface oxygen species by nitrogen, resulting in a similar surface modification as in the plasma case. The comparison of XPS data and water contact angle studies suggest that the activated surfaces show a reorientation of macromolecular fragments in the surface‐near region depending on the polarity of the phase with which they are in contact. Under ultra‐high vacuum (UHV) conditions, the surface tends to lower its surface energy, while in contact with the aqueous phase, subsurface polar groups orientate outwards, which enables the formation of hydrogen bonds.

Learning to teach and teaching to learn about Robotics Professionalization for inclusive technology education integrating theory and practice - Osnabrügge, Malin; Schemel, Nele; Schneider, Lea; Schröer, Franz; Tenberge, Claudia (Zukünfte technischer Bildung)

Selbstwirksamkeitserwartungen zur methodischen Gestaltung eines gemeinschaftsorientierten und partizipativ-verfahrensorientierten Unterrichts: Entwicklung von Kurzskalen zur schulischen Demokratiebildung - Wehde, Janis (Zeitschrift für Bildungsforschung)

Evaluation of anti-adhesive and corrosion protection properties of TiAlSiN-magnetron-sputtered films for applications in polymer processing - Theile-Rasche, Chantal; Wang, Fuzeng; Prüßner, Tim; Huck, Marten; Steinrück, Hans-Georg; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Thin Solid Films)